2010
DOI: 10.7326/0003-4819-153-12-201012210-00003
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea for Treating the Common Cold

Abstract: Background Echinacea is widely used to treat common cold. Objective To assess potential benefits of echinacea as common cold treatment. Design Randomized controlled trial with four parallel groups: 1) no pills, 2) placebo pills (blinded), 3) echinacea pills (blinded), or 4) echinacea pills (open-label). (NCT00065715) Setting Community-based trial. Participants People aged 12 to 80 years with new onset common cold. Interventions Extracts of Echinacea purpurea and E. angustifolia root were used to make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 66 publications
0
86
1
3
Order By: Relevance
“…We chose a design that would assess 2 kinds of pill-related placebo effects (no pill vs blinded to placebo, and blinded to vs open-label treatment) and would also provide evidence regarding potential effects of physician-patient interaction. Our review of the relevant literature, 33 detailed methods, 34 and results related to echinacea 35 and physician-patient interaction 36 are available elsewhere.…”
Section: Pl Ac Eb O Ef Fec T S a Nd T He Co M M On Col Dmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose a design that would assess 2 kinds of pill-related placebo effects (no pill vs blinded to placebo, and blinded to vs open-label treatment) and would also provide evidence regarding potential effects of physician-patient interaction. Our review of the relevant literature, 33 detailed methods, 34 and results related to echinacea 35 and physician-patient interaction 36 are available elsewhere.…”
Section: Pl Ac Eb O Ef Fec T S a Nd T He Co M M On Col Dmentioning
confidence: 99%
“…Echinacea tablets included root extracts of Echinacea purpurea and E angustifolia. 35 Placebo and echinacea tablets measured 9 mm by 19 mm and were covered by reddish brown digestible coatings. Investigators and colleagues found it impossible to distinguish between the placebo and echinacea pills in terms of appearance, smell, or taste.…”
Section: Interventionsmentioning
confidence: 99%
“…3,[8][9][10] This study was approved by the University of Wisconsin-Madison Health Sciences Institutional Review Board, and informed consent was obtained from all the subjects. All human research guidelines of the United States Department of Health and Human Services and of the University of Wisconsin were followed.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Detailed methods and results are available elsewhere. 3,[8][9][10] Objective ARI Monitoring Nasal lavage was collected twice during the study, once at enrollment (day 1), and then again 2 days later (day 3). The NMI test is conducted by instilling a 5-mL aliquot of sterile isotonic medium into each nostril, followed by expression into a sterile container.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Echinacea is one of the most widely used herbal products in the United States (20). There are nine known different species of Echinacea, and they contain different chemicals, such as glycoproteins, polysaccharides, alkamides, and volatile oils (20).…”
mentioning
confidence: 99%